2023
DOI: 10.1101/2023.08.25.554764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The highly rugged yet navigable regulatory landscape of the bacterial transcription factor TetR

Cauã Antunes Westmann,
Leander Goldbach,
Andreas Wagner

Abstract: Transcription factor binding sites (TFBSs) are important sources of evolutionary innovations. Understanding how evolution navigates the sequence space of such sites can be achieved by mapping TFBS adaptive landscapes. In such a landscape, an individual location corresponds to a TFBS bound by a transcription factor. The elevation at that location corresponds to the strength of transcriptional regulation conveyed by the sequence. We developed anin vivomassively parallel reporter assay to map the landscape of bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…We close by describing some problems for future research that need to be addressed in order to apply the ideas presented here to large-scale empirical data sets such as those in [26,27]. First, the work on structured fitness landscapes should be generalized to sequence spaces with more than two alleles [86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We close by describing some problems for future research that need to be addressed in order to apply the ideas presented here to large-scale empirical data sets such as those in [26,27]. First, the work on structured fitness landscapes should be generalized to sequence spaces with more than two alleles [86].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the scale of the empirical fitness landscapes that can be explored using state-of-the-art high-throughput methods has increased enormously [19][20][21][22][23][24][25][26][27], but the factors determining how accessible these landscapes are remain largely unknown. For example, in an analysis of the affinity landscape spanned by the 15 point mutations separating the spike protein of the ancestral Wuhan strain of the SARS-CoV2 virus from the Omicron BA.1 variant, it was found that none of the 15!…”
Section: J Stat Mech (2024) 034003mentioning
confidence: 99%
“…Consequently, while our sensor system in EcN has been characterized and improved under aerobic conditions, there is substantial potential to enhance its sensitivity to lower, more physiologically relevant NO concentrations. Future studies could achieve this through advanced protein and promoter engineering techniques (e.g., directed evolution and combinatorial designs coupled with fluorescence-based screening methods [86][87][88][89] and by transitioning to anaerobic assays.…”
Section: Relationship Between Nanobody Production and Tnfα Concentrat...mentioning
confidence: 99%